Emotional Intelligence and Perceived Stress in Pharmacists Completing Post-Graduate Specialization Programs: A Cross-Sectional Study - anski, Dejan Sen; Marinkovi, Valentina; Georgiev, Andrijana Milo evi; Tadi, Ivana (Indian Journal of Pharmaceutical Education and Research, 2024)
Background: Emotional Intelligence (EI) has been recognized by the International Pharmaceutical Federation as a required competency for a pharmacist. This study aimed to compare EI and Perceived Stress (PS) levels in pharmacists who completed the post-graduate specialization program (the Case), and pharmacists who started the program (the Control group). Materials and Methods: Validated instruments measuring EI and PS were distributed online to participating postgraduates or alumni. All complete responses were analyzed; data from participants who had undergone previous EI training were excluded. Comparing the groups, additional EI domains’ subanalysis and their correlations with PS were made. Results: The overall response rate was 67.8%. There was no expected difference between the groups either in EI or in the PS levels, and the overall population reached means of 119.30±12.92 and 17.25±6.46, respectively. The highest EI levels were found in sales and marketing professionals in the pharmaceutical industry and the lowest in clinical pharmacy practitioners. EI and PS were highly negatively correlated (r=- 0,543), thus indicating that developing EI may have protective effects against stress. Subanalysis revealed the highest potential for stress-protective effects in the Emotional Self-Management and Emotional Self-Control subdomains (r=-0,528, r=-0,457, respectively). Conclusion: Given the expanded importance of EI development in pharmacy practice, the results of the study could be a basis for the specialization and continuing pharmacist education program creators to evaluate the curricula and propose changes in the methodologies, contents, and approaches in work to meet development needs of post-graduate pharmacists better. Further research should confirm the findings of the EI subanalysis.
Keywords: Emotional Intelligence; Perceived Stress; Pharmacy; Education; Specialization